IoT Data Collection Based on Social Network Models - Nataly Zhukova; Aung Myothaw; Man Tianxing; Mustafin Nikolay (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2020)
Nowadays, the heterogeneous network and devices of IoT become more complex and encountered several challenges. The investigations of social networks show that social network analysis methods are useful for the evolution and development of communication and social network models allow solving Internet-related problems. And they can provide more exact answers for complex problems. This article analyzes some methods of SNA from different aspects and investigated compatible methods to apply in IoT.